Influence of understory vegetation on fungal communities and 2,4,6-trichloroanisole contamination in raw cork from standing trees - Salvatore Seddaiu; Camilla Morittu; Luca Sarais; Antonio Mulas; Adriana Vilia; Gianfranco Marzeddu; Giuseppino Pira; Pino A. Ruiu; Edoardo Scali; Giovanni Piras; Francesca Meloni; Marco Serra; et al. (Forest Ecology and Management, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Detection and diversity of Phytophthora species from declining Quercus suber stands using both DNA metabarcoding and soil baiting techniques - Salvatore Seddaiu; Carolyn Riddell; Giovanni Piras; Pino A. Ruiu; Luca Sarais; Antonietta Mello; Peter J. A. Cock; Andrea Brandano; Sarah Green; Bruno Scanu (Mycological Progress, 2025)

Challenges to Mediterranean Fagaceae ecosystems affected by Phytophthora cinnamomi and Climate Change: Integrated Pest Management perspectives - Carmen Morales-Rodríguez; Andrea Vannini; Bruno Scanu; Pablo González-Moreno; Silvia Turco; Mounira Inas Drais; Andrea Brandano; Mari Ángeles Varo Martínez; Angelo Mazzaglia; Antonio Deidda; Adrián Cidre; José Gomes-Laranjo; et al. (Current Forestry Reports, 2025)

Phylogeography of the wide‐host range panglobal plant pathogen Phytophthora cinnamomi - Shankar K. Shakya; Niklaus J. Grünwald; Valerie J. Fieland; Brian J. Knaus; Jerry E. Weiland; Cristiana Maia; André Drenth; David I. Guest; Edward C.Y. Liew; Colin Crane; Tun‐Tschu Chang; Chuen‐Hsu Fu; et al. (Molecular Ecology, 2021)
Various hypotheses have been proposed regarding the origin of the plant pathogen Phytophthora cinnamomi . P . cinnamomi is a devastating, highly invasive soilborne pathogen associated with epidemics of agricultural, horticultural and forest plantations and native ecosystems worldwide. We conducted a phylogeographic analysis of populations of this pathogen sampled in Asia, Australia, Europe, southern and northern Africa, South America, and North America. Based on genotyping‐by‐sequencing, we observed the highest genotypic diversity in Taiwan and Vietnam, followed by Australia and South Africa. Mating type ratios were in equal proportions in Asia as expected for a sexual population. Simulations based on the index of association suggest a partially sexual, semi‐clonal mode of reproduction for the Taiwanese and Vietnamese populations while populations outside of Asia are clonal. Ancestral area reconstruction provides new evidence supporting Taiwan as the ancestral area, given our sample, indicating that this region might be near or at the centre of origin for this pathogen as speculated previously. The Australian and South African populations appear to be a secondary centre of diversity following migration from Taiwan or Vietnam. Our work also identified two panglobal, clonal lineages PcG1‐A2 and PcG2‐A2 of A2 mating type found on all continents. Further surveys of natural forests across Southeast Asia are needed to definitively locate the actual centre of origin of this important plant pathogen.

Antioxidant activity of methanol extract of Helichrysum foetidum Moench - Bruno Tirillini; Luigi Menghini; Lidia Leporini; Nadia Scanu; Stefania Marino; Giorgio Pintore (Natural Product Research, 2013)